A Comparative Analysis of the Financial Incentives of Two Distinct Experience-Rating Programs. Issue 7 (July 2016) - Tompa, Emile; McLeod, Chris; Mustard, Cam
Abstract : Objectives: The aim of this study was to compare the association between insurance premium incentives and claim outcomes in two different workers' compensation programs. Methods: Regression models were run for claim outcomes using data from two Canadian jurisdictions with different experience-rating programs—one with prospective (British Columbia) and another with retrospective (Ontario) adjustment of premiums. Key explanatory variables were past premium adjustments. Results: For both programs, past premium adjustments were significantly associated with claim outcomes, suggesting adjustments provided incentives for claims reduction. The magnitudes of effects in the prospective program were smaller than the retrospective one, though relative persistence of effects over time was larger. Conclusion: Having large and immediate employer responses to incentives may appear desirable, but insurers should consider the time required for employers to improve and sustain good practices, and create incentives that parallel such time lines.